A Study on Nickel Plating and Heavy Metal Wastewater Treatment Process: Improving waste water process quality in the aviation industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In all fields of production, wastewater is of critical significance. This water can therefore be processed and stored according to the necessary standards to maintain the protection of people and of the atmosphere regardless of the quality of waste water being heavy metals or oil. At present, the Manchester, Connecticut Aviation department of General Electric ( GE) works to enhance their waste water process quality.